Biologic and genetics aspects of chagas disease at endemic areas - Bellini, Marilanda Ferreira [UNESP]; Silistino-Souza, Rosana [UNESP]; Varella-Garcia, Marileila; Oliveira, Maria Tercília Vilela de Azeredo [UNESP]; Silva, Ana Elizabete [UNESP] (Hindawi, 2012)
The etiologic agent of Chagas Disease is the Trypanosoma cruzi, transmitted through blood-sucking insect vectors of the Triatominae subfamily, representing one of the most serious public health concerns in Latin America. There are geographic variations in the prevalence of clinical forms and morbidity of Chagas disease, likely due to genetic variation of the T. cruzi and the host genetic and environmental features. Increasing evidence has supported that inflammatory cytokines and chemokines are responsible for the generation of the inflammatory infiltrate and tissue damage. Moreover, genetic polymorphisms, protein expression levels, and genomic imbalances are associated with disease progression. This paper discusses these key aspects. Large surveys were carried out in Brazil and served as baseline for definition of the control measures adopted. However, Chagas disease is still active, and aspects such as host-parasite interactions, genetic mechanisms of cellular interaction, genetic variability, and tropism need further investigations in the attempt to eradicate the disease. Copyright 2012 Marilanda Ferreira Bellini et al.
Keywords: insecticide; lymphotoxin; molecular marker; organophosphate insecticide; transforming growth factor beta1; apoptosis; Brazil; cardiomyopathy; Chagas disease; coronary artery disease; cytokine production; digestive system; disease association; disease carrier; disease model; disease transmission; enzyme linked immunosorbent assay; esophageal squamous cell carcinoma; extracellular matrix; genetic polymorphism; health survey; heart disease; heart infarction; host cell; human; immune response; inflammation; life cycle stage; lymphocyte proliferation; megacolon; megaesophagus; nonhuman; oxidative stress; priority journal; review; single nucleotide polymorphism; T lymphocyte; Th1 cell; Trypanosoma cruzi; trypomastigote; vector control